Matens meglere Kontroll, kvalitet og kunnskap i den industrielle matens tid - Finstad, Terje; Kvaal, Stig; Stokland, Håkon B.; Østby, Per (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
How can we be sure that the food we buy in grocery stores won't make us sick? The institutions, laws and regulatory systems put in place to safeguard that food is safe to consume are the result of a long and complex process. This book takes a close look at that process and at how various actors and institutions - we call them 'food's facilitators' - have worked to ensure that the food we eat is fresh, healthy and safe. Food's Facilitators explores how modern foods and systems for food can be seen as the result of a series of administrative efforts and negotiations over how such food is produced. The authors examine laws and regulations, expertise, technologies, and media that contribute to binding the various modern industrialized food systems together. Their subject matter ranges from cookbooks and schools for housewives that have greatly influenced the Norwegian diet, to the industrial production of foods, freezer technology, date marking, and quality assessment. In addition, the authors look at the presentation of food on television as informational activity as well as debates about industrially produced ingredients and food products like margarine, artificial vanilla and farmed salmon. Through these examples the book illustrates how regulation, quality and information became necessary cornerstones in the evolution of the food industry. The authors have backgrounds in science and technology studies, history, anthropology, sociology and media science. The anthology has been edited by Terje Finstad, Stig Kvaal and Per Østby, all from the Department of Interdisciplinary Studies of Culture at the Norwegian University of Science and Technology (NTNU), and Håkon B. Stokland from the Norwegian Institute for Nature Research and NTNU's Department of Interdisciplinary Studies of Culture.